The necropolis of Abila of the Decapolis 2019-2021 - Al-Shorman, Abdulla, (Access archaeology., 2022)
A comprehensive synthesis of burial types, practices, and evidence for societal collapse in the growing field of bioarchaeology of Jordan, focusing on Abila of the Decapolis, the largest Graeco-Roman city in Jordan with a tremendous wealth of funerary remains.